Tackling Workforce Constraints : For Quality Care Amidst Absolute Infrastructure and Resource Constraints - World Bank Group (World Bank, Washington, DC, 2019)
Rural areas can face acute human resource shortages of doctors, nurses, and other health professionals. Health workers may perceive rural postings as low-status, offering few professional opportunities, and limiting their quality of life; in those situations, they cluster in relatively advantaged urban areas, leaving rural areas understaffed. Adequate staffing of rural areas will require better incentives for rural service; creative applications of the medical education system to better serve rural areas; and creative and appropriate task-shifting to prioritize health workers' scarce time.